2022
DOI: 10.1177/17454999221126712
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sustainability knowledge and attitude on sustainable intention and behaviour of Malaysian and Indonesian undergraduate students

Abstract: The study aims to examine Malaysian and Indonesian undergraduate students’ sustainability knowledge and sustainable attitudes and the impact on their sustainability intention and sustainable behaviour. An online survey was conducted using 953 respondents. The SmartPLS (Partial Least Squares) analysis demonstrated that sustainability knowledge and sustainable attitude significantly impact the students’ sustainability intention. Nevertheless, the effect of sustainability knowledge was less than the sustainable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
2
5
0
Order By: Relevance
“…Thus, this study provides a deeper understanding of the formation process underlying the willingness to purchase green clothing and helps enrich the literature on green consumption (Al Mamun et al. , 2018) and socially responsible behavior (Saleh et al. , 2022).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus, this study provides a deeper understanding of the formation process underlying the willingness to purchase green clothing and helps enrich the literature on green consumption (Al Mamun et al. , 2018) and socially responsible behavior (Saleh et al. , 2022).…”
Section: Discussionmentioning
confidence: 87%
“…, 2023). The impact of consumer knowledge on sustainable consumption varies considerably (Saleh et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the path coefficient between SK and attitude towards sustainability are recorded as β1=0.643 for the China sample, and β1=0.612 for the Malaysia sample. In similar context, Mohamad Saleh et al (2022) reported that SK can affect individuals' attitudes. Likewise, Kristiyono and Felim (2021) found that II has a positive and significant effect on environment attitude.…”
Section: Discussionmentioning
confidence: 94%
“…Malaysia set a goal of recycling 22% of total solid waste by 2020, although the current recycling rate is only about 5% [12]. Malaysia is lagging other wealthy countries, with recycling rates ranging from 30% to 47% [13]. In Malaysia, recycling is still not a common practise [14] and only a few people are following it religiously [15].…”
Section: Introductionmentioning
confidence: 99%